Community Partnership Program on Business of Food Processed Based on Cocoa Commodity - Pawana Nur Indah; Sri Widayanti; Indriya Radiyanto (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2018)
The purpose of Community Partnership Program (CPP) by the team from UPN "Veteran" East Java is to give a touch of science and technology on community activities. This CPP is intended to accelerate the creative economic activities of the community, by providing skills training in producing various cocoa-based foods and beverages. The method used in facilitating the improvement of skills of farmers community in micro enterprises in the processing of local products in the form of cocoa powder and fat is to conduct training Lecture and practice method is the basic theory in the operation of post harvest equipment of cocoa beans. In addition, the materials used in producing foods and drinks based on the hygiene of cocoa, nutritional value and the acceptable to the community and have an economical added value. It also provides mentoring with simple management materials and marketing to foster an understanding of entrepreneurship and the sustainability of business activities and the marketing of results. Based on the above facts, the purpose of the community service program that has been implemented is expected to increase the selling value of cocoa products, and the people's income in the region